Wykorzystanie transformacji zmiennych w budowie modelu regresyjnego - Trzęsiok, Joanna (Variables transformation models for regression, 2007)
In the paper two nonparametric methods for regression, using the variables transformation, are presented. One of them is the ACE (alternating conditional expectation) algorithm of Breiman and Friedman. The other is Tibshirani’s AVAS (additivity and variance stabilization) method. A numerical example for illustration and comparison is given.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1189, s. 156-167